Nanotechnology: The Emerging Science in Dentistry - Kovvuru, Suresh Kumar; Mahita, Vangala Naga; Manjunatha, BS; Babu, Buma Sudhakar; Mahita, Vangala Naga (Journal of Orofacial Research, 2019)
Predicting the future of any major technology is difficult. Nanotechnology or nanoscience refers to the research and development of an applied science at the atomic or molecularlevel (i.e. molecular engineering, manufacturing). Although the nanoscale is small in size, its potential is vast. Almost every area of human activity will be affected by futurenanotechnologies. Nanotechnology is also applied to various medical fields like pharmacological research, clinical diagnosis, supplementing immune system, cryogenic storage of biological tissues. The growing interest in the dental applications of nanotechnology is leading to the emergence of a new field called nanodentistry.